2019
DOI: 10.3390/chemengineering3010031
|View full text |Cite
|
Sign up to set email alerts
|

Improved Kinetics and Water Recovery with Propane as Co-Guest Gas on the Hydrate-Based Desalination (HyDesal) Process

Abstract: Water is a key resource for sustainable development and plays a crucial role in human development. Desalination is one of the most promising technologies to mitigate the emerging water crisis. Thermal desalination and reverse osmosis are two of the most widely employed desalination technologies in the world. However, these technologies are energy intensive. Clathrate-hydrate-based desalination (HyDesal) is a potential energy-efficient desalination technology to strengthen the energy–water nexus. In our previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…However, in this lab-scale study, we assume F h to be 1 for the calculation presented above. Similar calculations that support the use of an F h of 1 for labscale studies were reported by Babu et al, 6 Nambiar et al, 26 and Babu et al 28 The rate of water recovery was calculated by fitting the water recovery growth versus time from the nucleation point using the least-squares method.…”
Section: Calculation In Hydrate Formationsupporting
confidence: 62%
See 3 more Smart Citations
“…However, in this lab-scale study, we assume F h to be 1 for the calculation presented above. Similar calculations that support the use of an F h of 1 for labscale studies were reported by Babu et al, 6 Nambiar et al, 26 and Babu et al 28 The rate of water recovery was calculated by fitting the water recovery growth versus time from the nucleation point using the least-squares method.…”
Section: Calculation In Hydrate Formationsupporting
confidence: 62%
“…The amount of gas present in the solid hydrate phase at any time t was calculated by finding the difference between the initial number of moles present in the gaseous phase and the number of moles present in the gaseous phase at time t . The formula stated below can be used to find the total number of moles of gas consumed: where V CR is the volume of the gaseous phase in the reactor, P is the pressure inside the reactor, T is the temperature in the reactor, R is the universal gas constant, and z is the compressibility factor that was calculated using Pitzer’s correlation…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, He et al [35,227], Nambiar et al [228], and Chong et al [223], proposed a propanehydrate based desalination process using LNG cold energy. When compared to MSF, RO, and freezing techniques, Babu et al [229] demonstrated that this technology (the HyDesal process) can be economically attractive.…”
Section: Comparison Between Clathrate Formers For Hydrate-based Processmentioning
confidence: 99%